2018
DOI: 10.1002/cam4.1532
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of NDR1 contributes to metastasis of prostate cancer cells via activating epithelial‐mesenchymal transition

Abstract: The 5‐year survival rate decreases rapidly once the prostate cancer has invaded distant organs, although patients with localized prostate cancer have a good prognosis. In recent years, increasing numbers of reports showed that circulating tumor cells (CTCs) may play an important role in tumor metastasis and they have stronger potential of invasion and migration compared with their parental cells. In our previous investigation, we isolated CTCs from prostate cancer cell lines PC3. In this study, we found a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In this study, we used in vivo selection method to construct CTC cells according to previous reports 16 , 17 (Fig. 9 A).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we used in vivo selection method to construct CTC cells according to previous reports 16 , 17 (Fig. 9 A).…”
Section: Resultsmentioning
confidence: 99%
“…In this process, CTCs undergo a phenotypic change termed epithelial‐mesenchymal transition (EMT), in which the cells acquire a mesenchymal phenotype and thus become more aggressive and invasive . Moreover, researchers have proposed that EMT might provide CTCs with increased potential to survive in the different microenvironments encountered during metastasis through various ways, such as by enhancing metastatic competence, by increasing cell survival and early colonization, by promoting the formation of specific protective cytoskeletal structures and clusters of CTCs, and by promoting immune evasion . However, despite extensive experimental data, the exact role of EMT remains unclear, particularly regarding CTC immune evasion in the peripheral bloodstream.…”
Section: Introductionmentioning
confidence: 99%
“…However, a high STK38 expression was correlated with a poor clinical outcome, particularly in patients with LGG, gastric cancer and liver cancer, based on the Kaplan–Meier analysis. Past studies have reported that the STK38 expression was higher in primary prostate cancer than it was in metastasis cancer, and that it could be a potential tissue biomarker during tumor progression [ 20 ]. These results indicate that STK38 is a promising biomarker to estimate the clinical outcome of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, STK38 could reduce the proliferation and colony formation of glioblastomas [ 19 ]. STK38 was also discovered to inhibit the metastasis of prostate cancer both in vitro and in vivo [ 20 ].…”
Section: Introductionmentioning
confidence: 99%